Molecularly Imprinted Membrane Produced by Electrospinning for β-Caryophyllene Extraction - Moraes Segundo, João de Deus Pereira de; Moraes, Maria Oneide Silva de; Brito, Walter Ricardo; Matos, Robert S.; Salerno, Marco; Barcelay, Yonny Romaguera; Segala, Karen; Fonseca Filho, Henrique Duarte da; d’Ávila, Marcos Akira (Materials, 2022)
Molecularly imprinted membrane of β-caryophyllene (MIM–βCP) was fabricated incorporating β-caryophyllene molecularly imprinted polymer nanoparticles (βCP–NP) into polycaprolactone (PCL) fibers via electrospinning. The βCP–NP were synthesized by precipitation polymerization using the βCP as a template molecule and acrylic acid as a functional monomer in the proportion of 1:4 mol, respectively. Atomic force microscopy images and X-ray diffraction confirmed the nanoparticles’ incorporation into MIM–βCP. MIM–βCP functionalization was evaluated by gas chromatography. The binding capacity was 1.80 ± 0.05 µmol/cm2, and the selectivity test was performed with a mixing solution of βCP and caryophyllene oxide, as an analog compound, that extracted 77% of the βCP in 5 min. The electrospun MIM–βCP can be used to detect and extract the βCP, applications in the molecular sieve, and biosensor production and may also contribute as an initial methodology to enhance versatile applications in the future, such as in the treatment of skin diseases, filters for extraction, and detection of βCP to prevent counterfeiting of commercial products, and smart clothing with insect-repellent properties.
Keywords: Electrospinning; Acrylic monomers; β-caryophyllene; Nanopartículas